(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2019)
The article examines the existing approaches to the definition of the essence of environmental safety. Further development got the approaches to meaningful filling of ecological safety of the enterprise as a condition of protection from negative influences of the internal and external environment and the ability to quickly eliminate the threats, ensure their functioning on the basis of environmentally-oriented technical, technological and managerial innovations that make it impossible to cause harm to the environment, life and the health of people. Therefore, it is appropriate to consider the environmental safety of the enterprise from two points: the protection of the environment, people from the negative impact of the enterprise and the protection of the enterprise from environmental threats. It is proved that in Ukraine there are institutional preconditions for the implementation of tools for managing environmental safety in the enterprise management system. Namely, the processes of creating and implementing integrated quality management systems that meet the requirements of international standards are a prerequisite for the survival and sustainable development of enterprises, there is a sufficiently developed environmental law that involves international cooperation, an appropriate institutional structure is created and implemented that provides management of rational use, reproduction, protection and restoration of natural resources, state standards have been developed with requirements for the design documentation and ecological documentation from the assessment of environmental impact, environmental management system implemented as part of the overall system management. The proposed positioning of ecological safety in the enterprise management system as a criterion for making strategic decisions on: ensuring the compliance of all aspects of the functioning of enterprises with the requirements of the current environmental legislation and national and international environmental standards; provision of ecological rehabilitation and reproduction of disturbed ecosystems; use of ecologically safe resources and technologies; training of specialists who take ecologically-motivated management decisions; use in the system of management of enterprises of ecological management; formation of an effective system of informational and analytical support for environmental safety management.